2014
DOI: 10.1155/2014/701361
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Corneal Topography and Biomechanical Parameters after Use of Systemic Isotretinoin in Acne Vulgaris

Abstract: Purpose. We report the effect of isotretinoin on corneal topography, corneal thickness, and biomechanical parameters in patients with acne vulgaris. Method. Fifty-four eyes of 54 patients who received oral isotretinoin for treatment of acne vulgaris were evaluated. All patients underwent a corneal topographical evaluation with a Scheimpflug camera combined with Placido-disk (Sirius), ultrasonic pachymetry measurements, and corneal biomechanical evaluation with an ocular response analyzer at baseline, in the 1s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…These studies reported worsening of ocular surface parameters which support our result. 30,31 Treatment options for isotretinoin-associated MGD are limited and palliative to symptoms of OSD. Besides, there is no definitive method for restoration of the structure and function of damaged meibomian glands.…”
Section: Discussionmentioning
confidence: 99%
“…These studies reported worsening of ocular surface parameters which support our result. 30,31 Treatment options for isotretinoin-associated MGD are limited and palliative to symptoms of OSD. Besides, there is no definitive method for restoration of the structure and function of damaged meibomian glands.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Yildirim et al 2014 stated that corneal biomechanics (diameter and refractive index) did not change; however, changes in the tear film had affected the corneal surface. 6 …”
Section: Introductionmentioning
confidence: 99%
“…5 Yildirim et al 2014 stated that corneal biomechanics (diameter and refractive index) did not change; however, changes in the tear film had affected the corneal surface. 6 Ruiz-Lozano et al 2020 reported photophobia, corneal opacities, keratitis, refractive visual disturbances (day/ night vision disturbances), color vision impairment, and papilledema as rare adverse reactions. 4 There is a difference between the dermatological and the ophthalmological perceptions of isotretinoin.…”
Section: Introductionmentioning
confidence: 99%
“… 12 Isotretinoin is now widely used for the treatment of acne. 13 Acne is a common skin inflammatory condition 14 , 15 affecting approximately 9.4% of the world's population, making it the 8th most common disease worldwide. 16 Different treatments have been proposed for different severities of acne.…”
Section: Introductionmentioning
confidence: 99%
“… 23 There are reports of the effect of this medication on dry eye, 10 meibomian glands, 13 conjunctival goblet cells, 20 visual acuity, 22 retina, 24 intraocular pressure, 25 color vision, 26 and corneal topographic and biomechanical properties. 14 …”
Section: Introductionmentioning
confidence: 99%